Gentleman's agreement - Kazan, Elia; Hart, Moss, 1904-1961; Zanuck, Darryl Francis, 1902-1979; Peck, Gregory, 1916-2003; McGuire, Dorothy, 1918-2001; Garfield, John (Beverlly Hills : Twentieth Century Fox Home Entertainment, 2012)
Philip Green is commissioned to write a series of articles on anti-semitism for a progressive magazine. There must be a new angle, and to secure this he decides to pose as a Jew. It is then that he learns the meaning of intolerance, the petty insults and indignities which have to be suffered. He is in love with Kathy and tells her what he has done, but distrust and misunderstanding continually threaten to overrule their feelings for each other. A childhood friend, Dave Goldman, returns from overseas, and he, too, is exposed to the racial prejudice of Kathy and her friends. Even Green's young schoolboy son is made to suffer. We learn through restricted hotels, a doctor, a secretary, that every branch of American communal or business activity, contains a gentleman's agreement that Jews shall be excluded. Finally Dave persuades Kathy to overcome her doubts about the whole situation, and she and Green are reunited.
Originally released as a motion picture in 1947.
Based on the novel of the same name by Laura Z. Hobson.
Director of photography, Arthur Miller ; editor, Harmon Jones ; music, Alfred Newman ; art direction, Lyle Wheeler, Mark-Lee Kirk ; costumes designed by Kay Nelson.
Gregory Peck, Dorothy McGuire, John Garfield.
BBFO rating: Universal, suitable for all. Contains racism theme.
DVD ; region 2 ; full screen 4:3, presentation, aspect ratio 1.33.1 ; Dolby Digital 2.0.
Keywords: Antisemitism -- New York -- Drama; Impersonation -- New York (State) -- New York -- Drama; Journalists -- New York (State) -- New York -- Drama; Jews -- United States -- Social conditions -- 20th century -- Drama; Feature films; Fiction films